2012
DOI: 10.4068/cmj.2012.48.2.91
|View full text |Cite
|
Sign up to set email alerts
|

NosocomialPseudomonas putidaBacteremia: High Rates of Carbapenem Resistance and Mortality

Abstract: Previously, Pseudomonas putida was considered a low-virulence pathogen and was recognized as a rare cause of bacteremia. Recently, however, multidrug-resistant and carbapenem-resistant P. putida isolates have emerged, causing difficult-to-treat nosocomial infections in seriously ill patients. Currently, the outcome of multidrug-resistant or carbapenem-resistant P. putida bacteremia remains uncertain. Here, we report 18 cases of P. putida bacteremia with high rates of carbapenem resistance and mortality. From J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 19 publications
1
58
0
Order By: Relevance
“…All ExlA‐like toxins (including HplA) trigger the same death pathway in macrophages with activation of Caspase‐1 by the NLRP3 inflammasome and release of a high amount of IL‐1β during the infection. These finding is of importance considering the emergence over the three last decades of nosocomial infections caused by environmental Pseudomonas species (Yoshino et al ., ) particularly with multidrug resistant P. putida (Kim et al ., ). Until now, the virulence‐associated genes in P. putida were not clearly defined, and ExlA toxin may be a good candidate.…”
Section: Discussionmentioning
confidence: 97%
“…All ExlA‐like toxins (including HplA) trigger the same death pathway in macrophages with activation of Caspase‐1 by the NLRP3 inflammasome and release of a high amount of IL‐1β during the infection. These finding is of importance considering the emergence over the three last decades of nosocomial infections caused by environmental Pseudomonas species (Yoshino et al ., ) particularly with multidrug resistant P. putida (Kim et al ., ). Until now, the virulence‐associated genes in P. putida were not clearly defined, and ExlA toxin may be a good candidate.…”
Section: Discussionmentioning
confidence: 97%
“…Many cases of P putida infections such as nosocomial, pneumonia, wound, and septicemia were reported in the past decade. 22 Kim et al 23 reported 18 cases in which 77% were related to medical device infections (catheters) and 56% cases of immune-compromised patients.…”
Section: Seasonal Variation In Bacterial Population and Diversitymentioning
confidence: 99%
“…Consequently, its potential biotechnological application in a variety of different processes, including bioremediation of contaminated areas (2), biocatalysis of aromatic compounds (3), and production of bioplastics (4), or as an agent of plant growth promotion and plant pest control (5) is under investigation. In contrast, over the past decade P. putida has been identified to be an opportunistic human pathogen, causing difficultto-treat nosocomial infections, such as bacteremia, in seriously ill patients (6). The majority of these infections are due to highly multidrug-resistant P. putida strains mostly found in immunocompromised humans, such as newborns or neutropenic or cancer patients (7,8).…”
mentioning
confidence: 99%